2007
DOI: 10.1016/j.jinorgbio.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the active site of Mycobacterium tuberculosis KatG after disruption of the Met–Tyr–Trp cross-linked adduct

Abstract: Mycobacterium tuberculosis catalase-peroxidase (Mtb KatG) is a bifunctional enzyme that possesses both catalase and peroxidase activities and is responsible for the activation of the antituberculosis drug isoniazid. Mtb KatG contains an unusual adduct in its distal heme pocket that consists of the covalently linked Trp107, Tyr229, and Met255. The KatG(Y229F) mutant lacks this adduct and has decreased steady-state catalase activity and enhanced peroxidase activity. In order to test a potential structural role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…ARG104, TRP107, and HIS108 were located in the distal pocket of the active site. There are covalent linkages between TRP107 and TYR229 [23,24] . As shown in Figure 3, compound 1 , compound 2 , isoniazid, and pyrazinamide can all be accommodated in the binding pocket of Mtb KatG.…”
Section: Resultsmentioning
confidence: 99%
“…ARG104, TRP107, and HIS108 were located in the distal pocket of the active site. There are covalent linkages between TRP107 and TYR229 [23,24] . As shown in Figure 3, compound 1 , compound 2 , isoniazid, and pyrazinamide can all be accommodated in the binding pocket of Mtb KatG.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray structures revealed that KatGs possess unique covalent bonds formed among the side chains of three distal residues, Met-Tyr-Trp, which are located on the distal side of the haem active site. Mutagenesis studies confirmed that the Met-Tyr-Trp cross-link is required for catalatic activity (Regelsberger et al, 2000;Jakopitsch et al, 2004;Ghiladi et al, 2005;Kapetanaki et al, 2007;Zhao et al, 2010Zhao et al, , 2013. These structures have provided many insights into the structure and function of KatGs.…”
Section: Introductionmentioning
confidence: 82%
“…The Ser315Thr substitution in KatG impacts on the shifting of substrate binding chan nel from 6.0 to 4.7 Å [27]. Consequently the mutant failed to bind the INH, and subsequently decreased 160 times in the INH activation compared with KatGwt [14].…”
Section: Fig 4 Electrophoregram Of Katg Protein In Sds Page Proteimentioning
confidence: 99%
“…The mutant KatG Ser315Thr, that is commonly found in clinical isolates and associated with INH resistance, decreases the activities of catalaseper oxidase and INH oxidation [13,14]. The amino acid Ser315 in KatG is closely put in the active environ ment.…”
mentioning
confidence: 99%